IKZF1 Alterations and Therapeutic Targeting in B-Cell Acute Lymphoblastic Leukemia - Jonathan Paolino; Harrison Tsai; Marian H. Harris; Yana Pikman (2024)
IKZF1 encodes the transcription factor IKAROS, a zinc finger DNA-binding protein with a key role in lymphoid lineage development. IKAROS plays a critical role in the development of lineage-restricted mature lymphocytes. Deletions within IKZF1 in B-cell acute lymphoblastic leukemia (B-ALL) lead to a loss of normal IKAROS function, conferring leukemic stem cell properties, including self-renewal and subsequent uncontrolled growth. IKZF1 deletions are associated with treatment resistance and inferior outcomes. Early identification of IKZF1 deletions in B-ALL may inform the intensification of therapy and other potential treatment strategies to improve outcomes in this high-risk leukemia.